2020
DOI: 10.1088/1361-6463/ababcf
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of anodic erosion components and heat transfer efficiency for W and W80Ag20 in atmospheric-pressure arcs

Abstract: Based on the in situ diagnostic system and the digital image post-processing technique, quantifications of the anodic erosion components and heat transfer efficiency for tungsten and the W 80 Ag 20 material in arcs of argon, helium, and nitrogen were achieved. The leading vaporization of silver has been found to result in evidently lower anodic heat transfer efficiency and much smaller molten pools compared with those of the tungsten anode, but the intensive generation of silver vapor under the melt layer caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Through an in situ diagnostic system including surface temperature measurement and the fast imaging of the erosion process, Cui et al [35] found that the surface bubble explosion stemming from the Cu vapor inside the liquid tungsten layer is the main cause of splashing erosion of the W 70 Cu 30 anode, and the transition from evaporation-dominated mode to splashdominated mode is determined by the large difference between W and Cu in melting and boiling temperatures. The arc erosion characteristics of W 80 Ag 20 anode and pure tungsten anode are compared, and the results showed that W 80 Ag 20 anodes have lower anodic heat transfer efficiency, smaller molten pools, and higher splashing erosion owing to leading vaporization of silver [41]. Similar results were found in Mo 0.78 Cu 0.22 cathode under a DC vacuum arc discharge [42].…”
Section: Introductionmentioning
confidence: 55%
“…Through an in situ diagnostic system including surface temperature measurement and the fast imaging of the erosion process, Cui et al [35] found that the surface bubble explosion stemming from the Cu vapor inside the liquid tungsten layer is the main cause of splashing erosion of the W 70 Cu 30 anode, and the transition from evaporation-dominated mode to splashdominated mode is determined by the large difference between W and Cu in melting and boiling temperatures. The arc erosion characteristics of W 80 Ag 20 anode and pure tungsten anode are compared, and the results showed that W 80 Ag 20 anodes have lower anodic heat transfer efficiency, smaller molten pools, and higher splashing erosion owing to leading vaporization of silver [41]. Similar results were found in Mo 0.78 Cu 0.22 cathode under a DC vacuum arc discharge [42].…”
Section: Introductionmentioning
confidence: 55%
“…Then, the positive ions bombard the cathode, resulting in the jet of the cathode material. These materials are transferred to the anode along with the electron flow [ 42 ]. The crater and protrusion are the products of this material transfer process ( Figure S3b ).…”
Section: Resultsmentioning
confidence: 99%
“…As is well-known, the fluorine-containing groups (e.g., −CH 2 CH 2 CF 3 ) with high polarity could reduce the material's surface energy, and they thus are usually used to incorporate into the polysiloxanes to improve the material's chemical resistance in both nonpolar solvents and oils [31]. Previous studies have demonstrated that the chemical resistance of traditional silicone rubber could be enhanced by the partial replacement of methyl groups with some fluorine groups [32]; for example, fluorosilicone rubber [33][34][35]. However, there are few reports about the preparation of fluorosilicone rubber foam materials.…”
Section: Introductionmentioning
confidence: 99%